Motor learning and control: Concepts and applications - Magill, R. A.; Anderson, D. (McGraw-Hill, 2014)
Introductory study of motor learning and control for students who aspire to become practitioners in exercise science, physical education, and other movement-oriented professions. Magill opens with an introduction to motor skills and control, continues through attention, memory, and learning, and ends with a discussion of instruction, feedback, and practice methods. The text's strong research base, clear presentation and practical applications will help students build a solid foundation in motor skills and prepare them for further exploration on their own. The most notable change in this tenth edition of Motor Learning and Control is the addition of David Anderson as a co-author. David is a highly respected scholar and teacher at San Francisco State University. He teaches an introductory course in motor learning and control, as well as in motor development In addition, he brings with him a wealth of practical experiences from his background as a rugby player, coach, as well as consultant to sports teams in his native Australia. This new edition continues its two most distinctive features as an introductory motor learning and control textbook: its overall approach to the study of motor learning and control and the organization of the implementation of that approach. In every edition of this book, the overall approach has been the presentation of motor learning and control "concepts" to identify the common theme of each chapter. The concepts should be viewed as generalized statements and conclusions synthesized from collections of research findings. Following the concept statement is a description of a real-world application of the concept, which is then followed by discussions of specific topics and issues associated with the concept. An important part of these discussions are summaries of research evidence, on which we base our present knowledge of each topic and issue, as well as the implications of this knowledge for practitioners. The benefit of this organizational scheme is the presentation of motor learning and control as a set of principles and guidelines for practitioners that are based on research evidence rather than on tradition or "how things have always been done."Our goal for this edition continues to be to provide an introductory study of motor learning and control for students who aspire to become practitioners in various professions. As in previous editions the achievement of this goal involves the inclusion of research examples that demonstrate the evidence-based foundation for the motor learning and control concepts. It is important to note that the research examples are just that-examples; the intent of the discussion of research about a specific topic, therefore, is not to present an extensive review of the research literature or to investigate the various controversial views that may exist on a topic. New to this edition: Because an important goal of this book is to provide research evidence to support the various concepts and applications, it is essential to regularly update the research to maintain the book's relevance. As in previous editions, each chapter of the tenth edition includes updated research in the text, the A Closer Look boxes, and in the Related Readings sections. Research related to motor learning and control continues to increase, as evidenced by the ever-expanding amount of research articles and chapters published each year. Because of the availability of this new information, it is essential that an introductory textbook provide the most up to-date evidence available to support the numerous concepts and applications that can be derived from this research. But, the caveat here is to not overwhelm the reader with a litany of research studies. It is with this point in mind that we have as a primary intent to present examples of research studies that provide empirical support for the concepts discussed rather than to provide exhaustive reviews of the available research. There are also a lot of new or expanded topics in all chapters of the book.